Seven years in Tibet - Annaud, Jean-Jacques (Mandalay Entertainment, 1998)
Heinrich Harrer is an Austrian national and a Nazi sympathizer. He leaves Austria in 1939 to climb a mountain in the Himalayas. Through a series of circumstances (including POW camp), he and fellow climber Peter Aufschnaiter become the only two foreigners in the Tibetan holy city of Lhasa. There, Heinrich's life changes forever as he becomes a close confidant to the Dalai Lama.